MODEL DEKOMPOSISI ANALISIS JALUR: PENGARUH KAUSALITAS ANTAR VARIABEL PEMBENTUK KEMISKINAN DI PROVINSI NUSA TENGGARA TIMUR - Nur Imam Saifuloh; Sabir (Badan Pusat Statistik Provinsi NTT, 2022)
Poverty in developing countries mostly occupies in rural areas which the agricultural sector as main activity. In spite of this, agricultural land is decreasing as an effect of industrial and services activities. This study focuses on poverty in East Nusa Tenggara Province, Indonesia. By using decomposition model of path analysis, conversion of agricultural land and village funds have no significant effect on poverty even though the path is in accordance with the theory. Meanwhile, economic growth and dependency ratio have a significant effect on poverty which is mediated by the informal workers’ wage.